Orthotopic Patient-Derived Pancreatic Cancer Xenografts Engraft Into the Pancreatic Parenchyma, Metastasize, and Induce Muscle Wasting to Recapitulate the Human Disease. Issue 6 (July 2017) - Go, Kristina L.; Delitto, Daniel; Judge, Sarah M.; Gerber, Michael H.; George, Thomas J.; Behrns, Kevin E.; Hughes, Steven J.; Judge, Andrew R.; Trevino, Jose G.
Abstract : Objective: Limitations associated with current animal models serve as a major obstacle to reliable preclinical evaluation of therapies in pancreatic cancer (PC). In an effort to develop more reliable preclinical models, we have recently established a subcutaneous patient-derived xenograft (PDX) model. However, critical aspects of PC responsible for its highly lethal nature, such as the development of distant metastasis and cancer cachexia, remain underrepresented in the flank PDX model. The purpose of this study was to evaluate the degree to which an orthotopic PDX model of PC recapitulates these aspects of the human disease. Methods: Human PDX-derived PC tumors were implanted directly into the pancreas of NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ mice. Tumor growth, metastasis, and muscle wasting were then evaluated. Results: Orthotopically implanted PDX-derived tumors consistently incorporated into the murine pancreatic parenchyma, metastasized to both the liver and lungs and induced muscle wasting directly proportional to the size of the tumor, consistent of the cancer cachexia syndrome. Conclusions: Through the orthotopic implantation technique described, we demonstrate a highly reproducible model that recapitulates both local and systemic aspects of human PC.